2020
DOI: 10.1002/pros.23979
|View full text |Cite
|
Sign up to set email alerts
|

miR‐30a inhibits androgen‐independent growth of prostate cancer via targeting MYBL2, FOXD1, and SOX4

Abstract: Background: Castrate-resistant prostate cancer (CRPC) is an aggressive and lethal disease. The pathogenesis of CRPC is not fully understood and novel therapeutic targets need to be identified to improve the patients' prognosis. has been demonstrated to be a tumor suppressor in many types of solid malignancies. However, its role in androgen-independent (AI) growth of prostate cancer (PCa) received limited attention as yet. Methods:The clinical association of miR-30a and its potential targets with AI growth was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Recent reports indicated that FOXD1 plays a oncogenic effect in several types of cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and likely associates with the mechanism for radioresistance [ 37 ]. In this study, our data showed that FOXD1 is capable of directly regulating the expression of G3BP2 , which is capable of inhibiting p53 activity through a direct binding, which may further promote p53 nuclear export via increasing p53 sumoylation [ 38 ] and serves as a poor prognostic marker in prostate cancer patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that FOXD1 plays a oncogenic effect in several types of cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and likely associates with the mechanism for radioresistance [ 37 ]. In this study, our data showed that FOXD1 is capable of directly regulating the expression of G3BP2 , which is capable of inhibiting p53 activity through a direct binding, which may further promote p53 nuclear export via increasing p53 sumoylation [ 38 ] and serves as a poor prognostic marker in prostate cancer patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PCa also continues to increase in Asian countries, including China, where patients with PCa are often confirmed at local late stage or metastatic stage and are, thus, greatly affected by a mortality‐to‐incidence ratio that is as high as 50% (Akaza, Onozawa, & Hinotsu, 2017; Yu & Zhou, 2020). Although androgen deprivation therapy (ADT) shows some therapeutic effect in the treatment of late stage/advanced PCa, the tumor will still develop into more aggressive castrate‐resistant PCa after ADT failure, resulting in a relatively low overall 5‐year survival rate about 26–30% (X. Li et al, 2020; Ritch & Cookson, 2018). Moreover, the pathogenesis and progression of PCa has not been clearly clarified due to its complicated association with many genetic alterations and epigenetic interactions (Antognelli, Mezzasoma, Mearini, & Talesa, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…FOXD1 is involved in the progress of many diseases, including several tumor types [9][10][11] . Previous studies have shown the oncogene role of FOXD1 in glioma 12 , non-small cell lung cancer 13 , and breast cancer 14 , etc.…”
Section: Discussionmentioning
confidence: 99%